Transforming learning : instructional and assessment strategies for leadership education - Guthrie, Kathy L.; Jenkins, Daniel M. (Contemporary perspectives on leadership learning., 2020)
"In this companion manual to The Role of Leadership Educators: Transforming Learning, this text was developed to fill a significant resource gap in leadership education. In response to this gap, as well as leadership educators' call for professional development related to teaching and learning, this text is grounded in the college teaching and leadership education literature. Filled with 60 learning activities for diverse contributors, this book offers a hands-on resource for leadership educators to use when facilitating leadership learning opportunities. Each learning activity includes learning outcomes, activity instructions, facilitation notes, and additional resources offered by the author. The text is organized by the pedagogical methods covered in The Role of Leadership Educators: Transforming Learning. Pedagogical methods covered include Discussion, Case Studies, Reflection, Team-Based Learning, Service Learning, Self- and Peer-Assessments, Role-Play, Simulation, Games, and Art. Each chapter contains six learning activities for each pedagogical method, four focused in instructional strategies (curricular, co-curricular, technology-enhanced, followership-focused) and two in learning assessment strategies (curricular and co-curricular)"--